Urban governance and its role in shaping low-income household food security in Bulawayo, Zimbabwe - Maphosa, Mandlenkosi; Moyo, Philani (Frontiers in Sustainable Cities, 2025)
Urbanization in Sub-Saharan Africa (SSA) is accelerating without corresponding economic growth, leading to urban poverty and food insecurity. This paper examines the role of urban governance in shaping food security among low-income households in Bulawayo, Zimbabwe. Using a mixed-methods design that combined a household survey (n = 398) with in-depth interviews, focus group discussions, and key informant interviews in Ward 28, Bulawayo, Zimbabwe, the study assessed how urban governance shapes the four dimensions of food security. It highlights how governance structures influence food availability, access, utilization, and stability at the household level. Using proxy indicators such as the Household Food Insecurity Access Score (HFIAS), Months of Adequate Household Food Provisioning (MAHFP), and the Household Dietary Diversity Score (HDDS), the study reveals that most households experience mild to moderate food insecurity. The HDDS analysis indicates a nutrition transition, with high consumption of cereals, fats, sugars, and processed foods, raising concerns about dietary adequacy despite higher diversity scores. Stability, a key food security dimension, showed households’ relative self-sufficiency, but COVID-19 disrupted this stability. Interestingly, no clear relationship was found between household income and food security, suggesting the significant impact of systemic factors. Governance elements like land allocation, infrastructure, and services significantly influence household food choices and behaviors. The findings emphasize the need for inclusive urban governance and participatory planning to address food insecurity in urban areas of Zimbabwe.